Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf. (1st April 2020) - Bedford, Jacob; Ostle, Clare; Johns, David G.; Atkinson, Angus; Best, Mike; Bresnan, Eileen; Machairopoulou, Margarita; Graves, Carolyn A.; Devlin, Michelle; Milligan, Alex; Pitois, Sophie; Mellor, Adam; et al.
Abstract: Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, 'diatom' and 'meroplankton' lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans. Abstract : Trends in abundance and correlations with sea surface temperature were mapped for six key plankton lifeforms. Coastal and inshore time‐series were compared with multi‐decadal offshore trends from the Continuous Plankton Recorder.